'Not hard to sway': a case study of student engagement in two large engineering classes. (4th July 2018) - Shekhar, Prateek; Borrego, Maura
ABSTRACT: Although engineering education research has empirically validated the effectiveness of active learning in improving student learning over traditional lecture-based methods, the adoption of active learning in classrooms has been slow. One of the greatest reported barriers is student resistance towards engagement in active learning exercises. This paper argues that the level of student engagement in active learning classrooms is an interplay of social and physical classroom characteristics. Using classroom observations and instructor interviews, this study describes the influence of the interaction of student response systems and classroom layout on student engagement in two large active-learning-based engineering classrooms. The findings suggest that the use of different student response systems in combination with cluster-style seating arrangements can increase student engagement in large classrooms.